ANALISIS PENGARUH KEAHLIAN MENJUAL TENAGA PENJUAL, DAN KUALITAS PELAYANAN GLAXO SMITH KLEINE TERHADAP KINERJA TENAGA PENJUAL - Hendriyanto, Asepta (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2012)
This study aims to test the effects of salesperson selling skills and service quality of sales person to salesperson sales performance. .The study used several customer of Glaxo Smith Klein as sample. Data analyze instrument used by the writer is SPSS 17. Data analyze result shows that the research model has well appropriateness and all hypothesis of the study are able to be evidenced. Summary said that salesperson selling skill, and service quality are positively effected to salesperson performance. Based on the result of the study, managerial implication given to the company is suggestion or input to management of Glaxo Smith Klein to give more concern at the salesperson selling skill, as it is the most dominant factor effected to salesperson sales performance. Keywords: salesperson performance, service quality, salesperson selling skill